From a garbage crisis to sustainability strategies: The case study of Naples' waste collection firm. (10th June 2018) - Lamboglia, Rita; Fiorentino, Raffaele; Mancini, Daniela; Garzella, Stefano
Abstract: Sustainability strategies have become a key element in various firms. Although many studies have discussed the sustainability adoption process, a gap exists between studies with pure deductive theorizing and those that focus on empirical practices by comparing the main theoretical models with empirical evidence. Additionally, there has been little research on the sustainability process for public service organizations such as waste collection firms. This paper focuses on how sustainability strategies are developed in waste collection firms. Specifically, we analyse an extreme case, the waste collection firm of the municipality of Naples (WCFMN). This company is a public utility firm owned by the municipality of Naples. Analysing a distinct case provides the opportunity to gain insights and explore how firms develop an overall sustainability strategy, from its motivations to its effects. Our findings support legitimacy theory while providing food for thought about the relation between legitimacy theory and utility maximization theory. Legitimacy theory explains the sustainability adoption process of the WCFMN, whereas utility maximization theory should inform future strategies. Thus, we enrich the ongoing debate about the connections between sustainability drivers, strategies, actions and performance. These findings will help executives and managers of public service organizations to identify and exploit the most effective means of managing the adoption of corporate social responsibility. Highlights: The study analyses the sustainability strategy adoption process, from drivers to performance. The case study analysis supports and extends the Legitimacy Theory. Waste collection firms should pay special attention to sustainability practices. Garbage crises could paradoxically provide opportunities to improve corporate sustainability. Findings suggest effective ways of coping with corporate sustainability.